Development of the Roe Deer–Fascioloides magna Association over Time - Anja France Noëlle Renée Buet; Miljenko Bujanić; Krešimir Krapinec; Ivica Bošković; Anđelko Gašpar; Dean Konjević (Pathogens)
The trematode Fascioloides magna is originally a parasite of North American deer species. Upon its arrival to Europe, F. magna met new intermediate and final hosts. Depending on the type of host, the clinical picture, pathological findings, epidemiology and outcome can vary significantly. As an aberrant host, it was long believed that the roe deer (Capreolus capreolus) fails to develop pseudocysts, and therefore the infected animal dies before the parasite can mature and start to produce eggs. In this study, 676 roe deer livers were collected in Croatia during the hunting years of four consecutive years (2019–2023) in Bjelovar-Bilogora County (BB), and 184 livers were collected from Zagreb County (ZG) in the hunting year 2022/2023. Livers were analysed macroscopically and on a cut surface for lesions and any developmental stage of F. magna according to a standard protocol. The mean prevalence of infected livers during the whole study period was 12.86% in BB and 3.8% in ZG. No pseudocysts were detected in samples from ZG, while there was an increasing trend of pseudocyst presence over time in BB. The occurrence of pseudocysts in infected livers showed a rapid increase after the hunting season 2019/2020, before becoming constant (at approx. 40%). The odds of finding pseudocysts ranged between 2.7 (OR = 2.7317, CI 95% 0.3108 to 24.0095, p = 0.365) and 2.9 (OR = 2.9167, CI 95% 0.3163 to 26.8924, p = 0.345) times higher in later years compared to 2019/2020. Similarly, an increasing trend (though less pronounced) was observed in the numbers of livers simultaneously containing pseudocysts and fluke migratory stages. The results indicate a potential change in the roe deer–F. magna association, where an increasing number of roe deer are forming pseudocysts and can survive even multiple infections.